Psychologically based therapies to improve lung functioning in students with asthma. Issue 2 (2nd April 2016) - Maykel, Cheryl; Bray, Melissa; Gelbar, Nicholas; Caterino, Linda; Avitia, Maria; Sassu, Kari; Root, Melissa
Abstract : Asthma is a common, chronic respiratory disease that can be costly to both society and the individual. In addition to increased absenteeism, children with asthma may also be at a greater risk for developing comorbid anxiety and depression. Various complementary psychological treatments have been effective at reducing both asthmatic symptoms and psychological distress. Although the research in the area of mind-body treatments as it pertains specifically to persons with asthma is still developing, this article will describe several promising alternative treatment methods, many of which have already been, or could be easily be applied for use in a school setting.